Evaluación de la activación de linfocitos de ratas desnutridas durante la lactancia - Cortés Barberena, Edith (Universidad Autónoma Metropolitana, 2009)
Malnutrition is distributed widely throughout the World and is a particular problem in developing countries. Actually, recent studies estimate that 10 million of children younger than 5 years of age die in developing countries; more than 50% of deaths in children are attributed to conditions preventable: the malnutrition contributes to these deaths. The objective of the present study was to evaluate the activation of spleen lymphocytes in vitro and proliferation of spleen cells in vivo of rats with moderate and severe malnutrition experimentally induced during lactation period compared with well-nourished rats. The percentage of T, B, NK cells and in T lymphocytes, T4 and T8 were determinate in malnourished rats of moderate and severe level and control rats, obtained of peripheral blood and spleen, assessed by flow cytometry. The effect of both levels of malnutrition on activation of splenic T cells in vitro of malnourished rats of second and third degree, assessed by flow cytometry. It was analyzed the effect of malnutrition on cell proliferation on splenic cells of suckling rats in vivo. The malnutrition was induced during the lactation period until weaning. The degree of malnutrition was established according to the classification used for children: the number was categorized as mild or first degree when the weight deficit reached 10– 25%; moderate or second degree (MN2nd) when the weight deficit reached 25–40%; and severe or third degree (MN3rd) when the weight deficit was greater than 40% of that of age-matched control rats (WN). The moderate and severe malnourished rats were studied. The results showed that both malnourished groups of rats have lower numbers of leukocytes, monocytes and lymphocytes on peripheral blood. The CD4+ lymphocytes subpopulation was affected on blood and spleen. Response to mitogen stimuli of phytohaemagglutinin (PHA) was evaluated in splenic lymphocytes. Expression of cell surface activation markers CD71+ and CD25+ was evaluated, to determinate the response of T cells. Both groups of malnourished rats showed a significant decrease in the percentage of CD3+CD71+ and CD3+CD25+ cells at 24 h post-activation with PHA. There was a positive correlation between spleen weight and the percentages of spleen cells expressing CD71 (R = 0.97) receptors. No significant difference was observed between the moderate and severe malnourished rats. Cell proliferation was studied by detection of BrdU incorporation and flow cytometry. The method involves calculation using flow cytometry data of BrdU incorporation (green fluorescence, FITC-labelled anti-BrdU-DNA antibody) and total DNA content (red fluorescence, propidium iodide). After 21 days of age, BrdU at the dose of 1 mg/g body weight was administered by intraperitoneal injection. Flow cytometry was used to detect BrdU labeling in proliferating splenocytes. Distribution of cells in each cycle cells was analyzed. The proportion of cells in G1 phase was higher in malnourished rats than well-nourished rats, but no significant difference was observed between the moderate and severe malnourished rats, but no significative difference was observed in borh malnourished groups. No significant difference was observed in proportion of cells in S phase between well-nourished and malnourished rats. Percentage of G2/M was lower in both groups of malnourished rats. The labelling index of BrdU+ (LI), Sphase duration (TS) and potential doubling time (Tpot) were calculated. The LI of cells was lower in both groups of malnourished rats than WN rats. The obtained TS was not different in both malnourished rats to WN rats. Tpot was significantly higher in both malnourished groups. In conclusion, the results of this study suggest that moderate malnutrition is as bad as severe malnutrition with effects in different parameters of immune system: lymphocytes proportion of blood and spleen, lymphocyte activation and cell proliferation in spleen. The data explain, in part, the increased susceptibility increased associated with malnutrition.; La desnutrición está ampliamente distribuida en el mundo y es un problema en países en desarrollo. Los estragos en los niños pueden ser devastadores. En la actualidad se reconoce que aproximadamente 10 millones de niños menores de 5 años mueren cada año en países en desarrollo, de las cuales más del 50% se puede atribuir a enfermedades prevenibles: la desnutrición contribuye a estas muertes. El objetivo general de este estudio fue evaluar la activación in vitro de linfocitos de bazo y la proliferación in vivo de células de bazo de ratas con desnutrición de segundo y tercer grado inducida experimentalmente por competencia de alimento durante la lactancia a los 21 días de edad y compararlo con ratas bien nutridas. Para esto se cuantificaron, por medio de citometría de flujo, el porcentaje de los linfocitos T, B, NK y, dentro de los T, los T4 y T8 en ratas desnutridas de segundo y tercer grado y testigos bien nutridos, obtenidos a partir de sangre periférica y los extraídos del bazo. Se determinó, por citometría de flujo, el efecto de ambos grados de desnutrición sobre la activación de linfocitos de bazo de ratas desnutridas de segundo y tercer grado y testigos sanos en cultivos primarios in vitro. Se determinó el efecto de la desnutrición sobre la proliferación in vivo de células de bazo de ratas de 21 días de edad. Se indujo la desnutrición durante la lactancia y al final de esta, se clasificaron en tres grados, según el déficit de peso: primer grado o leve (déficit mayor al 10% y menor a 25); segundo grado o moderada (déficit de 25% y menor de 40%); tercer grado o grave (déficit de 40% o más). Se estudiaron los grupos de ratas con desnutrición moderada y grave. Los resultados mostraron que ambos grupos de ratas desnutridas tienen una cantidad menor de leucocitos, monocitos y linfocitos en sangre periférica, en comparación con las ratas testigo. Se observó que de los linfocitos T la subpoblación afectada fue la CD4+ (cooperadores) en sangre y en bazo, lo cual repercutió en la población de linfocitos T. La activación de los linfocitos de bazo en cultivo se evaluó estimulándolos con el mitógeno fitohemaglutinina (PHA). La respuesta se midió determinando el incremento en la expresión de los marcadores CD71 y CD25, que se expresan al estimular a los linfocitos T con la PHA, o con un antígeno. La proporción de linfocitos CD3+CD71+ y de CD3+CD25+ (activados) de ambos grupos de ratas desnutridas fue menor que la de ratas bien nutridas (p < 0.05). Además, se observó una correlación positiva entre el peso del bazo y el porcentaje de células que expresaron el receptor CD71 (R=0.97). No se observó diferencia significativa entre las ratas desnutridas de segundo y tercer grado. La proliferación de las células de bazo se determinó administrando bromodesoxiuridina (BrdU) y su incorporación se detectó con anticuerpos monoclonales anti-BrdU, conjugados con fluoresceína (FITC), el contenido de ADN total por yoduro de propidio y se evaluaron por citometría de flujo. La proporción de células en fase G1 fue mayor en las ratas desnutridas que en las bien nutridas, pero no se observó diferencia entre ratas con desnutrición moderada y grave. La proporción de células en la fase S fue mayor en las ratas bien nutridas, que en las desnutridas. La proporción de células en fase la G2/M fue menor en ambos grupos de ratas desnutridas que la del grupo de las bien nutridas. El índice de incorporación de BrdU (LI) fue menor en las células de bazo de ratas desnutridas, la duración de la fase S (TS) no mostró diferencia significativa entre los grupos y el tiempo de duplicación de la población celular (Tpot) se incrementó en ambos grupos de de ratas desnutridas. Los resultados muestran que la desnutrición moderada tiene efectos tan importantes como la desnutrición grave, que involucraron la proporción de linfocitos en sangre y bazo, la activación de linfocitos y la proliferación celular en bazo. Los resultados son una evidencia por la que, en parte, se puede explicar la susceptibilidad a infecciones asociada a la desnutrición.